Oil extraction from spent coffee grounds (SCG) using soxhlet extraction employing methanol as solvent / Nur Qistina ‘Aliaa Sukri - Sukri, Nur Qistina ‘Aliaa (2023)
The roasted and ground seeds of the tropical evergreen coffee plant are used to make the beverage known as coffee. Along with water and tea, coffee is one of the three most consumed beverages worldwide due to its composition that contain caffeine that will enhances nerve system and brain activity of human. Due to it large consuming, it will produce around 50% of coffee production and producing around 6 to 10 million tonnes of coffee waste which is spent coffee grounds (SCG) annually. These large production of SCG will lead to the increasing of landfill waste thus, will contribute to the environmental pollution. Therefore, an experiment were conducted to extract the oil from SCG using Soxhlet extraction method employing methanol as a solvent at different cycles. The purpose of this experiment is to determined the optimum percentage yield of the extracted oil. The highest percentage yield obtained is 9.903% at extraction time 95 min in cycle 5.